The economic burden of providing health insurance : how much worse off are small firms? - Eibner, Christine (Technical report (Rand Corporation), 2008)
More than 60 percent of nonelderly Americans receive health-insurance (HI) coverage through employers, either as policyholders or as dependents. However, rising health-care costs are leading many to question the long-term viability of the employer-based insurance system. Concerns about the economic burden of providing HI are particularly acute for small businesses, which are both less likely than larger firms to offer HI and more sensitive to price when deciding to offer insurance. Small firms may have difficulty containing costs due to their limited bargaining power and their inability to hir.